Intercultural communication competence among migrant workers in Malaysia: a critical review and an agenda for future research - Dalib, Syarizan; Mohamad, Bahtiar; Nadeem, Muhammad Umar; Halim, Haslina; Ramlan, Sayang Nurshahrizleen (Frontiers in Communication, 2023)
Intercultural communication competence (ICC) has been identified as an important area of study given today's increasing diversity in many societies. While it is acknowledged that there are already ICC studies and models available in the literature, most, if not all, addressed the ICC of expatriates or sojourners. Studies, as well as models that specifically address ICC of migrant workers are scanty. Hence, the paper intends to highlight the crucial need for a better understanding on the issues related to ICC by providing a comprehensive and critical review of studies on ICC. This enables for the proposition of a conceptual framework of ICC that is specific to migrant workers working in Malaysian due to their crucial importance to the country's economy. The proposed conceptual framework considers antecedents that include sensation seeking, ethnocentrism, attitude toward other cultures and motivation to engage in intercultural communication as the antecedents of ICC. Meanwhile, cross-cultural adjustment is proposed as the consequence of ICC. The proposed conceptual model would be useful in bridging the budding literature of ICC by highlighting the skills needed by migrant workers, which will consequently, facilitate their adjustment and enable them to perform their work successfully in Malaysian culture.